The effect of velocity-based contraction strength training on performance in female 400m athletes - Krit, S.; Sriket, N.; Phongampai, M. (International Journal of Disabilities Sports and Health Sciences, 2024)
This study aims to compare the differences in strength training at velocity of muscle contraction in 400-meter runners. The sample group consisted of 12 female athletes who participated in the Thailand National Sports competition qualifiers in 2023. The group was divided into two: the first group underwent strength training at a fast muscle contraction rate with 80 bpm, while the second group trained at a normal muscle contraction rate with 40 bpm. The training lasted for 8 weeks, and after a 2-week post-training period, both groups were tested by swapping strength training programs. They were tested for 400-meter speed, strength from finding the 1 RM of Leg curl, Leg extension, and Leg press measured in kilograms, and explosive power from Squat jump, Countermovement jump, and Long jump. The data collected was analyzed to find the average, standard deviation, and one-way ANOVA with a statistical significance level set at .05. From the research's results, it was found that percentage change muscle contraction rates differs significantly between the two strength training formats: one with fast muscle contraction and the other with normal- muscle contraction rate (1.04±0.02 and 1.02±0.02, respectively) at a significance level of .05. Additionally, the strength and explosive power percentage change also significantly differ between the two strength training formats. Therefore, based on this study, it is possible to utilize the fast muscle contraction rate strength training format to enhance the athletic performance of athletes.